Adaptation using IM Adapt of an evidence-based lifestyle intervention to support the management of metabolic-dysfunction associated steatotic liver disease among Hispanic/Latino adults - Natalia I. Heredia; Sylvia A. Ayieko; Serena A. Rodriguez; Serena A. Rodriguez; Jessica P. Hwang; Lorna H. McNeill; Maria E. Fernandez; Maria E. Fernandez (Frontiers in Public Health)
The high prevalence of metabolic-dysfunction associated steatotic liver disease (MASLD), formerly non-alcoholic fatty liver disease (NAFLD), necessitates the availability of an evidence-based intervention to manage the condition among patients to prevent severe chronic liver disease and other cardiometabolic-related illnesses. IM Adapt (Intervention Mapping for Adaptation) is a systematic approach for planning modifications in interventions to improve fit and potential effectiveness. Following this stepped approach, we conducted interviews with the target population, conducted a literature review, solicited expert advice, and created a logic model describing expected program outcomes for the new population and setting. We searched for, selected, and adapted an evidence-based intervention suitable for the target population. Given the similarities in management strategies between type 2 diabetes mellitus and MASLD (i.e., weight loss from physical activity and dietary changes), the National Diabetes Prevention Program’s Prevent T2 curriculum was selected and adapted to Hispanic/Latino patients with MASLD. We used Evidence-Based Intervention (EBI) Mapping to develop a logic model of change for the Prevent T2 curriculum, and we then compared this logic model to the one developed for our hypothetical program. Differences in content and delivery were noted, and changes were made to the curriculum. This resulted in the proposed Healthy Liver/Hígado Sano program. We also used IM Adapt to help plan for the implementation and evaluation of the program. Future testing of this intervention will determine its utility in improving the management of MASLD among Hispanic/Latino patients.